Using genome-wide data to ascertain taxonomic status and assess population genetic structure for Houston toads (Bufo [= Anaxyrus] houstonensis) - Shashwat Sirsi; David Rodriguez; Michael R. J. Forstner (Scientific Reports)
Abstract The Houston toad (Bufo [= Anaxyrus] houstonensis) is an endangered amphibian with a small geographic range. Land-use changes have primarily driven decline in B. houstonensis with population supplementation predominant among efforts to reduce its current extinction risk. However, there has been historic uncertainty regarding the evolutionary and conservation significance of B. houstonensis. To this end, we used 1170 genome-wide nuclear DNA markers to examine phylogenetic relationships between our focal taxon, representatives of the Nearctic B. americanus group, and B. nebulifer, a sympatric Middle American species. Phylogenetic analyses indicate B. houstonensis is a taxon that is distinct from B. americanus. We corroborated such genetic distinctiveness with an admixture analysis that provided support for recent reproductive isolation between B. americanus and B. houstonensis. However, ABBA-BABA tests for ancient admixture indicated historic gene flow between Nearctic species while no signal of historic gene flow was detected between Nearctic and Middle-American species. We used an admixture analysis to recognize four Management Units (MU) based on observed genetic differentiation within B. houstonensis and recommend captive propagation, population supplementation, and habitat restoration efforts specific to each MU. Our results re-affirm the evolutionary novelty of an endangered relict.